Decoding emotional resilience in aging: unveiling the interplay between daily functioning and emotional health - Guo, Minhua; Xu, Songyang; He, Xiaofang; He, Jiawei; Yang, Hui; Zhang, Lin (Frontiers in Public Health, 2024)
Emotional Problems (EPs) are a pressing concern for middle-aged and elderly populations, prompting attention in public health. This study examines Activities of Daily Living (ADL) as predictors for EPs. Using 2018 China Health and Retirement Longitudinal Study (CHARLS) data (n=9766, aged 45+), ADL was assessed with the Barthel Index (BI). Statistical analyses explored ADL-EPs correlation, validated by machine learning algorithms. Results indicate a negative ADL-EPs correlation, confirmed by algorithms (SVM-AUC=0.700, DT-AUC=0.742, LR-AUC=0.711). Impaired ADL heightens EPs susceptibility